What types of publicly listed firms evade taxes? Evidence from China - CHOW, Travis K. (Institutional Knowledge at Singapore Management University, 2018)
Using the mandatory disclosure of detected corporate tax evasion cases in China, we examine the types of publicly listed firms that evade taxes. We use a bivariate probit model to account for the partial observability of tax evasion. Our regression results are different from those using the reduced form probit model that ignores the partial observability of tax evasion. Our results are also different from those of prior research on the determinants of corporate tax avoidance using the effective tax rate (ETR) as a proxy for tax avoidance, suggesting that ETR may not be a good proxy for aggressive tax avoidance.